O discurso ambiental no programa de desenvolvimento regional sustentável da região sudoeste da Bahia : reflexos sobre o planejamento territorial no período de 2000 a 2005 - Cruz, Cláudia Anastácio Coelho (2009)
The sustainable development discourse has been incorporated into the political programs resulting in many different strategies. The search for a different kind of development is in the core of the discussion about sustainability; therefore, it is based on the participation of different social groups in order to achieve ecological, economical and social goals. With the purpose to contribute to environmental politics analysis, considering the sustainability discourse analysis under empirical and conceptual point of view as a methodological alternative, this research aimed to analyze the environmental discourse in Sustainable Regional Development Program – SRDP in Southwestern Bahia, Brazil and its reflects on territorial planning between 2000 and 2005. This research was carried out with bibliographic review, survey of cartographic documents; search for executed actions, elaboration of thematic maps, interview with government, private company and civil society representatives, and the analysis of collected dates. The SRDP pointed out five sustainable dimensions: environmental, economic-social, historic-cultural, scientific-technologic and political-institutional. However, the sustainable discourse defended by the PDRS valorizes essentially the economic competitively with repercussions on territorial ordination. The investigation into community participation in SRDP Bahia permitted to verify the weak actuation of associations and syndicates on problems discussion concerning the solutions to regional development supported by sustainability. This reality showed the devaluation of the democratic management. Among the actions focused on sustainability, it was pointed out the production and commercialization of regional products as a result of direct action of local associations. According to official report analysis, the government actions focused on sustainability occurred in different state segments, each working in isolation. According to the stakeholders’ report, these actions occurred in vertical form and predominantly incompatible with regional community reality. Thus, the Program served to legitimate a sustainability discourse to attend just a few stakeholders. The results permitted clarify the interest in competition on nature appropriation, with repercussion on target-territory of this environmental policy. Finally, it is essential to admit the necessity of reflection on environmental policies on which the sustainability should have a multidimensional character, and should be focused on legitimate participation in decision-making, as well as in management of production in order to attend social needs.